Perineal stapled prolapse resection in combination with Thiersch operation for relapsed rectal prolapse: a case report - Teppei Kamada; Hironori Ohdaira; Junji Takahashi; Yoshinobu Fuse; Wataru Kai; Keigo Nakashima; Yuichi Nakaseko; Norihiko Suzuki; Masashi Yoshida; Takeo Usui; Yutaka Suzuki (Surgical Case Reports, 2021)
Abstract Background Treatment options for complete rectal prolapse include over 100 procedures. In previous reports, operative rectal prolapse repair, regardless of the technique by perineal approach, was associated with high recurrence rates. However, there is no consensus on the optimal surgical procedure for relapsed rectal prolapse. Case presentation A 97-year-old woman was admitted to our hospital with a chief complaint of complete rectal prolapse measuring > 5 cm. The patient had a history of laparoscopic anterior suture rectopexy without sigmoid resection under general anesthesia for complete rectal prolapse one year prior. The patient’s postoperative course was uneventful. However, her dementia worsened (Hasegawa’s dementia scale: 5/30 points) after the first operation. Further, moderate-to-severe aortic valve stenosis was first diagnosed with heart failure 6 months after the operation. Nine months after the initial surgery, she experienced a recurrence of complete rectal prolapse measuring approximately 5 cm. Considering the coexistence of advanced age, severe dementia, and aortic valve stenosis, surgery under general anesthesia was not indicated. Perineal stapled prolapse resection in combination with the t operation was planned because of its minimal invasiveness and shortened hospital stay. The procedure was performed by a team of two surgeons in the jack knife position, under spinal anesthesia. The prolapse was cut along the long-axis direction with three linear staplers and resected along the short-axis direction with four linear staplers. The cross-section of the linear stapler was reinforced with 3-0 Vicryl sutures. After rectal resection, the Thiersch operation using 1-0 nylon thread 1 cm away from the anal verge was additionally performed. The operative time was 24 min, and intraoperative blood loss was 1 mL. The postoperative course was uneventful. Three months after the operation, no recurrence was observed, and defecation function was good with improvements of Wexner score. Conclusions Perineal stapled prolapse resection in combination with the Thiersch operation could be a useful option for patients with relapsed rectal prolapse and with poor general condition, who are not indicated for other surgical procedures.